LANGUAGES AND CULTURAL RELATIONS IN THE GLOBALIZATION PROCESSES (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The article discusses the complex and dynamic relationship between language and culture in the context of globalization. Globalization has led to a closely interconnected world of cultures and languages, and this has had an impact on linguistic diversity, cultural exchange, identity, and the role of dominant languages in shaping global discourse. The article examines case studies and theoretical frameworks to explore the connections between language and culture. It highlights how globalization facilitates cultural exchange but also poses challenges to linguistic diversity and cultural preservation. The article also discusses how languages serve as conduits of culture and identity, and the impact of dominant global languages. It explores the challenges and opportunities presented to linguistic and cultural diversity, and how they can be addressed. Through an interdisciplinary lens, the article illuminates the multifaceted dynamics of languages and cultural relations in an increasingly globalized world. Overall, the article emphasizes the importance of understanding the relationship between language and culture in the context of globalization, and the need to preserve linguistic and cultural diversity.